THE EFFECTIVENESS OF RECYCLE WASTE MODULE BASED ON ECOPRENEURSHIP TO INCREASE THE ENTREPRENEURIAL INTEREST - Ekris Sutiyanti; Widowati Budijastuti (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2018)
Learning goals achievement based on the 2013 curriculum, students need a learning program with soft skill development that should be trained. One of the soft skills that students need is the entrepreneurial skill. Entrepreneurial education applies the principle of entrepreneurship through ecology learning (ecopreneurship). This research aimed to describe the effectiveness of recycling waste module based on ecopreneurship to increase entrepreneurial interest. This research used a 4D model. The trials activity was limited to 20 students X grade in SMA Negeri 1 Kedamean. The research design was a pretest-posttest control group design. The data collection technique used: (1) ratting score questionnaire; (2) qualitative responses questionnaire. The research data was analyzed by (1) Gain score; (2) descriptive qualitative. The research result: (1) Increased entrepreneur interest of students after using ecopreneurship module with an average score of Gain score 0.31 with the medium category; 2) Students response to ecopreneurship module was very good with an average value of 98.75%. Key Words: Module, ecopreneurship, entrepreneurial interest, waste recycle .